ELEKTRODEKOLORISASI LIMBAH CAIR INDUSTRI SARUNG TENUN SAMARINDA MENGGUNAKAN ELEKTRODA PbO2/Pb DARI AKI BEKAS - Ramadani, Desi Fidyah; Wirawan, Teguh; Widodo, Nanang Tri (JURNAL ATOMIK; Vol 10 No 1 (2025), 2025)
Electrodecolorization of liquid waste from the Samarinda woven sarong industry using PbO 2 /Pb electrode has been conducted. The purpose of this study was to decolorize woven sarong wastewater samples using the electrodecolorization method using lead dioxide (PbO 2 ) as the anode and lead (Pb) as the cathode. Electrodecolorization is carried out by varying working potential, Na 2 SO 4 electrolyte concentration, time and electrode distance. The dye concentration was determined using a UV-Vis spectrophotometer. The research results showed that the optimum conditions for electrodecolorization of woven sarong wastewater samples were using PbO 2 /Pb electrodes, namely with a working potential of 6 volts, a Na 2 SO 4 electrolyte concentration of 0.25 M, a time of 60 minutes, and a distance of 1 cm. The percentage of decolorization of Samarinda woven sarong wastewater samples using PbO 2 /Pb electrodes, at maximum conditions was 98,75%.